Latest development on the membrane formation for gas separation - Ismail, Ahmad Fauzi; Ridzuan, Norida; Abdul Rahman, Sunarti (Songkla University, 2002)
The first scientific observation related to gas separation was encountered by J.K Mitchell in 1831. However, the most remarkable and influential contribution to membrane gas separation technology was the systematic study by Thomas Graham in 1860. However only in 1979, membrane based gas separation technology was available and recognized as one of the most recent and advanced unit operations for gas separation processes. Membrane is fabricated by various methods and the parameters involved to a certain extent are very complicated. The phase inversion technique that is normally employed to produce membranes are drylwet, wet, dry and thermal induced phase separation. Other techniques used to produce membrane are also reviewed. This paper reports the latest development in membrane formation for gas separation. The route to produce defect-free and ultrathin-skinned asymmetric membrane is also presented that represents the cutting edge technology in membrane gas separation process